2006
DOI: 10.1002/glia.20420
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced astrocytic reaction and increased vascular permeability in the rat cerebellum

Abstract: Hypoxia is an important factor linked to induction of vascular leakage and formation of brain edema. In this connection, astrocytes associated closely with the blood vessels are deemed to be involved. This study investigated the response of astrocytes to hypoxia in the adult rat cerebellum, and along with this, the integrity of the blood-brain barrier (BBB) was assessed using fluorescent and electron dense tracers. In rats subjected to hypoxia, mRNA and protein expression of hypoxia inducible factor-1alpha (HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 51 publications
(53 reference statements)
8
140
1
1
Order By: Relevance
“…Statistical analysis is referred to levels of ␤-actin expression. *, p Ͻ 0.05; **, p Ͻ 0.01; ***, p Ͻ 0.001. cells the AQP-5 gene is up-regulated by HIF through interaction with hypoxia-responsive elements in the promoter (40), and AQP-4 mRNA has also been shown to be up-regulated by hypoxia in astrocytes (41). This could explain why humans (14) and mice (12,13) lacking AQP-1 do not exhibit major gross physiological alterations related with either water or O 2 metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis is referred to levels of ␤-actin expression. *, p Ͻ 0.05; **, p Ͻ 0.01; ***, p Ͻ 0.001. cells the AQP-5 gene is up-regulated by HIF through interaction with hypoxia-responsive elements in the promoter (40), and AQP-4 mRNA has also been shown to be up-regulated by hypoxia in astrocytes (41). This could explain why humans (14) and mice (12,13) lacking AQP-1 do not exhibit major gross physiological alterations related with either water or O 2 metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…15 A recent study in rats demonstrated that under hypoxic conditions, upregulation of HIF1a was associated with AQP4 increase in the brain, and that HIF-1a inhibitor can benefit neurological outcomes by reducing water content or brain swelling rates with downregulation of AQP4. [36][37][38] Cigarette smoke exposure can upregulate water content and AQP4 expression, which is likely triggered by HIF-1a.…”
Section: Figmentioning
confidence: 99%
“…However, other contributory factors could include increased expression of the aquaporin 4 water channel in astrocytes (30), and downregulation of angiopoietin-1, an important accessory protein for neovascularization and producing stable blood vessel structure, which is also correlated with increased blood-brain barrier leakage (31).…”
Section: Microvasculature and Fetal Hypoxiamentioning
confidence: 99%